Study of Leucaena leucocephala seed biomass as a new source for cellulose / Maryam Husin - Maryam , Husin (2019)
Leucaena leucochephala is a tropical tree with many uses in which the application is primarily for wood production and the seeds for animal feed. The high growth rate and relatively abundant availability of Leucaena leucocephala make it suitable as a source for various applications such as production for energy, source of polysaccharides, livestock fodder, paper production, erosion control, and shade. Limited research has been conducted on Leucaena leucocephala seeds (LLS) due to more focus given to the wood parts for paper and pulp production. Therefore, the main objectives of this research are to optimize cellulose production with respect to the conditions used during the isolation process. Then, the feasibility of using cellulose as new source for the bioethanol application is evaluated. In general, lignocellulosic biomass is processed for bioethanol production through four major operations which are pretreatment process to remove hemicellulose and lignin, hydrolysis of cellulose or hemicellulose to produce sugar monomer, fermentation to convert sugars to ethanol, and separation or purification. The experimental result showed that boiling water under reflux can be considered as one of the cost effective and environmentally friendly methods to disrupt and remove some non-cellulosic compound. Isolation of cellulose by acid method is simple and fast compared to the alkaline method which is time consuming and requires bleaching step. Cellulose from LLS has been successfully isolated by using 80% acetic acid and 65% nitric acid to yield 33% cellulose. Microcrystalline and cellulose nanocrystals were further prepared from the LLS-cellulose via the acid hydrolysis method and yielded 71% and 27% respectively. The physicochemical and structural properties of the produced materials were characterized using Fourier-transform infrared spectroscopy (FTIR), morphology of the materials by field emission scanning electron microscopy (FESEM), cellulose crystallinity index (CI) by x-ray diffractometer (XRD), thermal stability behavior by thermal gravimetric analysis (TGA), and differential scanning calorimetry (DSC). Based on the characteristics of micro and nano cellulose isolated, they could be used as precursors for other industrial applications such as fillers in bio composite. In the next step, the cellulose obtained was converted into glucose by dilute acid hydrolysis using sulphuric acid by varying the concentration, volume, and reaction time. Sugar composition was analyzed using the phenol-sulfuric acid method and pre-column derivatization HPLC techniques. The yield of glucose ranging from 70 – 85 % could be obtained from cellulose isolated from waste seeds of Leucaena leucocephala. Response surface methodology (RSM) was used for modelling and optimization of ethanol production from glucose obtained from LLS by Saccharomyces cerevisiae. Interaction of three independent variables, pH of media (4.0-5.5), volume of inoculumn (8-14 ml), and fermentation time (48-168 hr) in the batch fermentation was investigated. The optimization condition for bioethanol production from Leucaena leucocephala seeds was found with inoculum volume of 12.92 ml, pH of solution at 4.87, and fermentation time of 117.68 hr with predicted bioethanol yield of 22.18% and volume 9.89 ml.